Chronic pancreatitis: definition, etiology, investigation and treatment - Mayerle, Julia; Hoffmeister, Albrecht; Werner, Jens; Witt, Heiko B. G.; Lerch, Markus M.; Mössner, Joachim (Deutsches Ärzteblatt, 2013)
Background: Chronic pancreatitis has an annual incidence of 23 per 100 000 population in Germany, where it accounts for about 10 000 hospital admissions per year. The disease shortens the life expectancy of its sufferers by an average of 23%. It most commonly affects men aged 20 to 40. - Methods: A systematic search for pertinent literature retrieved 19 569 publications, 485 of which were considered in the creation of this guideline, including 67 randomized controlled trials (RCTs). A consensus conference reached agreement on a total of 156 definitions and recommendations. - Results: The identification of genetic risk factors for pancreatitis is now well established. The diagnosis is made mainly with ultrasonography of the pancreas; if the findings are uncertain, further studies can be performed, including endosonography and endosonographically assisted fine-needle puncture for the examination of small foci of disease. Computed tomography and MRI/magnetic resonance cholangiopancreatography are supplementary diagnostic methods. Endoscopic retrograde cholangiopancreatography is now used almost exclusively for treatment, rather than for diagnosis. 30% to 60% of patients develop complications of chronic pancreatitis, including pseudocysts, bile-duct stenosis, or medically intractable pain, which can be treated with an endoscopic or surgical intervention. Patients with steatorrhea, a pathological pancreatic function test, or clinical evidence of malabsorption should be given pancreatin supplementation. The head of the pancreas should be resected if it contains an inflammatory pseudotumor. - Conclusion: The management of patients with chronic pancreatitis requires close interdisciplinary collaboration, as it can be treated medically and endoscopically as well as surgically. ►Cite this as: Mayerle J, Hoffmeister A, Werner J, Witt H, Lerch MM, Mössner J: Clinical Practice Guideline: Chronic pancreatitis—definition, etiology, investigation and treatment. Dtsch Arztebl Int 2013; 110(22): 387-93. DOI: 10.3238/arztebl.2013.0387